2019
DOI: 10.24310/ejfbejfb.v9i2.5265
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative innovation in the family SME: conceptualization, goals, and success factors

Abstract: In a constantly changing environment, collaborative innovation enables the knowledge creation and new product designs, the improved efficiency of the production process and the reduction of time-to-market. However, the achievement of such results in the family SME depends mainly on the unique characteristics of this type of organization, which in turn represent the most widespread kind of business worldwide. Therefore, the objective of this article is to analyze how the composition of the management team, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Within the family business literature, most of the research has explored the outcomes associated with KS. These studies have found that the extent to which family and non-family employees share knowledge within family firms is positively related to the organization's technological capabilities (Zahra et al, 2007), entrepreneurial orientation (Barroso Martı ´nez et al, 2016;Pittino et al, 2018), innovation (Arzubiaga et al, 2019;Calabro `et al, 2019;Casprini et al, 2017;Del Vecchio et al, 2019;Price et al, 2013), internationalization (Fang et al, 2018) and performance (Jaskiewicz et al, 2013).…”
Section: Generation In Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the family business literature, most of the research has explored the outcomes associated with KS. These studies have found that the extent to which family and non-family employees share knowledge within family firms is positively related to the organization's technological capabilities (Zahra et al, 2007), entrepreneurial orientation (Barroso Martı ´nez et al, 2016;Pittino et al, 2018), innovation (Arzubiaga et al, 2019;Calabro `et al, 2019;Casprini et al, 2017;Del Vecchio et al, 2019;Price et al, 2013), internationalization (Fang et al, 2018) and performance (Jaskiewicz et al, 2013).…”
Section: Generation In Controlmentioning
confidence: 99%
“…The first group of studies explore KS between family members and how exchanges between family members impact the succession process (Bra ¨nnback et al, 2008;Cabrera-Su arez et al, 2001;Cabrera-Su arez et al, 2018) or the capabilities that the firm develops (Chirico andSalvato, 2008, 2016;Fang et al, 2018). The second group of studies have focused on how KS within the family firm affects organizational processes such as entrepreneurial orientation of the firm (Pittino et al, 2018), entrepreneurial legacy (Jaskiewicz et al, 2015), innovation (Arzubiaga et al, 2019;Casprini et al, 2017;Calabro èt al., 2019) and technological capabilities (Zahra et al, 2007). However, an important gap in the exploration of KS in family firms is understanding how the family system impacts KS within family firms.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, we use socioemotional wealth (SEW), defined as the non-financial dimensions of firms that meet families' affective needs, such as, for example, the family identity or the capacity to exert family influence (Gómez-Mejía et al, 2007), as the main theoretical approach to elaborate our reasoning. Given that family firms' willingness to safeguard SEW varies according to the generational stage in which firms are, and according to the level of family management (Arzubiaga et al, 2019;Fang et al, 2018), we argue that these variations will be reflected in important family firms' differences towards R&D collaboration breadth and consequently, in the manner in which the latter is translated into innovation efficiency.…”
Section: Introductionmentioning
confidence: 95%
“…In today's rapidly changing and innovative business environments, R&D collaboration breadth and innovation efficiency have become vital strategic imperatives for the competitiveness or even the survival of firms (Feng et al, 2022;Lyu et al, 2020;Serrano-Bedia et al, 2019). Although existing evidence suggests that the link between R&D collaboration breadth and innovation efficiency is relatively established in the literature (Hernandez-Vivanco et al, 2018;Stefan & Bengtsson, 2017;Un & Asakawa, 2015), it does not necessarily hold true in the family firm sphere (Arzubiaga et al, 2019;Manzaneque et al, 2018). This is particularly striking considering that family firms, which, defined as firms predominantly dominated by a family with a focus on keeping family control over generations (Zellweger, 2017), stand for two-thirds of all firms in the world and generate the overwhelming majority of jobs and GDP in most economies worldwide (Family Firm Institute, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The overlap and interaction of the family and business subsystems and the desire to keep the business under family control throughout generations have a significant influence when family firms set their goals since they think about both the business and the family (Aparicio et al , 2017). In this sense, given that innovation and internationalization strategies involve complex tasks and uncertainty (Arzubiaga et al , 2019b; Ray et al , 2018; Tsao and Lien, 2013), family firms may avoid these high-return strategies if they perceive a high risk of damaging their SEW (Gómez-Mejía et al , 2007, 2014; Ray et al , 2018; Sciascia et al , 2015). However, at the same time, given that family members are loss averse toward their SEW, they can also engage in risky business decisions to protect their SEW, even if they expect their financial wealth to diminish (Gómez-Mejía et al , 2014).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%